Automatic Generation of Number Series Reasoning Items of High Difficulty - Sun, Luning; Liu, Yanan; Luo, Fang (Frontiers in Psychology, 2019)
Number series reasoning items have been frequently used in educational assessment. This study reviewed the previous literature investigating features relating to item difficulty and developed a new automatic generator for number series reasoning items. Ninety-two items were generated and administered to 466 students. The results showed that the test achieved acceptable reliability. Items requiring two arithmetic operations were of particularly high difficulty. All stimulus features implemented in the automatic item generator proved to be significant predictors of item difficulty, explaining 77% of the total variance. This suggests that the automatic number series reasoning item generator was capable of generating items of considerably predictable difficulty. More importantly, the resulting items covered a wide range of difficulty levels, meeting the particular need for items of high difficulty.